Importance of packaging in wine preferences: findings in a Chilean wine zone - Araya-Pizarro, Sebastián (2020)
The wine market in Chile is characterized by the low internal consumption, the high concentration of the production in area (South-Central region) and the strong sectorial rivalry, aspects that emphasize the importance of designing effective commercial strategies based on the attributes that explain consumer preferences, especially at the point-of-sale. The weight of four value attributes on the consumer's purchase decision was analyzed through the application of a survey to 388 subjects of the Coquimbo Region (northern Chile wine zone) and the estimation of a multivariate model. The results show that the relative importance of packaging is 28% (bottle: 9% and cup: 19%); price, 29%, and strain, 43%. In particular, corked wines with concave base, strain Cabernet Sauvignon and high price are preferred. It was revealed that the consumer’s buying behavior focuses on quality (price as a sign of quality) and does not manifest preference for regional production. Also, it was observed that packaging importance is directly linked with the consumer’s age and inversely with the income level. The findings are expected to allow local wine producers to improve the positioning of their wines in the market.